Particle physics as a way to bring different cultures to work together in science. (14th October 2016) - Mikenberg, G.
Abstract: Science has traditionally played an important role in sharing knowledge among people. Particle physics, with its large experiments, has shown that one can not only share the knowledge among different cultures, but that one can also work together to achieve this knowledge. The present article gives a few examples where this has been possible among people that are sometimes in conflict situations.